Analisis problem solving berdasarkan toeri dewey dalam - Dhaniera Evin Sanjaya; Alfi Muawwanahtul Ula; Ani Nur Sholihah; Farzhanda Afyatur Rahmah; Syintiya Ayu Rohmani; Rissa Prima Kurniawati (Universitas PGRI Madiun, 2026)
This study aims to analyze the problem-solving abilities of fifth-grade elementary school students in solving geometry problems based on John Dewey’s theory of problem-solving. The study employed a descriptive qualitative approach with subjects selected based on variations in academic ability. Data were collected through geometry tests and documentation, then analyzed based on John Dewey’s stages: recognizing the problem, defining the problem, developing a solution, testing the solution, and drawing conclusions. The results showed that high-ability students were able to carry out all stages well, while students with moderate abilities still experienced difficulties in the stages of testing solutions and drawing conclusions. Meanwhile, low-ability students struggled with identifying problems and developing solutions. This study demonstrates that John Dewey’s theory can be used to analyze students’ problem-solving abilities in solving geometry problems.